Organosilicon-polyurethane foam encapsulating material and preparation method thereof

By using silicone-polyurethane composite potting materials in new energy battery packaging materials, the shortcomings of existing materials in terms of moisture and heat resistance, impact resistance and bonding strength are solved, and the high safety performance of the battery module in harsh environments is achieved. .

CN119431715APending Publication Date: 2025-02-14SHANGHAI CHUANGLAN NEW MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202310963104.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing new energy battery packaging materials have shortcomings in terms of moisture and heat resistance, impact resistance and bonding strength, resulting in insufficient safety performance of the battery module under high temperature, low temperature and shock vibration.

Method used

A silicone-polyurethane composite potting material is used, which consists of components A and components B, and the curing speed, bonding strength and weather resistance of the material are improved through specific formulations and processes.

Benefits of technology

It realizes the high-temperature and low-temperature stability of the battery module, enhances the resistance to shock and vibration, effectively blocks the leakage of the battery cell and the heat of ignition, and improves the overall safety performance of the battery module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431715A_ABST
    Figure CN119431715A_ABST
Patent Text Reader

Abstract

The organosilicon-polyurethane foam encapsulating material is composed of a component A and a component B. The component A comprises sucrose initial polyether polyol, sorbitol initial polyether polyol, a water-containing alcohol amine foaming agent, a catalyst and a halogen-free flame retardant, and the component B comprises an NCO-terminated polysiloxane-polyurethane prepolymer, silicone oil and a diluent. Wherein the water-containing alcohol amine foaming agent comprises isopropyl alcohol di-sec-butyl alcohol amine, a mixture of isopropyl alcohol sec-butyl alcohol amine and water. The two-component encapsulating material is used for encapsulating a new energy battery module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organosilicon-polyurethane foam potting material and a preparation method and application thereof. The (foam) potting material (which forms a potting glue after curing) is used for the assembly and packaging of new energy battery modules (or battery packs), belonging to new energy battery packaging technology. Background Art

[0002] Recently, with the rapid development of battery energy storage technology, new energy batteries have become the hottest and most cutting-edge technology field through various packaging (PACK) forms. New energy batteries are widely used in new energy vehicles, energy storage battery packs, fast battery replacement and other industries.

[0003] Major battery cell manufacturers and packaging manufacturers at home and abroad are constantly increasing the energy density of battery packs. Safety issues such as leakage, short circuit, and explosion are increasingly becoming a shackle restricting the development of the new energy industry.

[0004] In the process of new energy battery packaging (packing), many composite functional materials will be used, for example: structural adhesive is used for bonding and fixing of battery cells; thermal conductive adhesive is used to dissipate heat when the battery pack is working, and they play a protective role in the new energy battery pack.

[0005] However, in the new energy industry, whether it is the automotive industry, fast battery replacement, or energy storage industry, battery packs (battery components) are core components. Only by ensuring the safety of battery modules can the safety of life and property of users be guaranteed.

[0006] The durability, permanence, flame retardancy, impact resistance and non-corrosiveness of the potting material are the guarantee of the safety of new energy battery packs.

[0007] At present, in the energy storage, commercial vehicle and application directions of cylindrical batteries, due to the difficulty of production and the cost of potting products, most of the cells do not have potting functional materials. In the application process of battery packs, due to the quality problems of the products themselves and the application environment, some cells are damaged, leaked, short-circuited and caused severe fires, causing huge losses to the personal and property safety of users.

[0008] Currently, the molding (curing) time of silicone potting glue is long and the efficiency is low; the density of silicone potting glue is large and the application cost is high; the bonding effect of silicone potting glue is poor.

[0009] In addition, epoxy resin potting glue is not resistant to temperature differences, has too high hardness, and has weak ability to withstand hot and cold shocks.

[0010] CN114316882A discloses a polyurethane heat-conducting potting glue and a preparation method thereof. The potting glue comprises components A and B, wherein component A comprises 20-60 parts of a polyol polymer, 10-30 parts of a mixture containing silane-modified polyols, 40-110 parts of a heat-conducting powder, and a water absorbent; component B comprises 10-30 parts of an isocyanate compound, 1-10 parts of a mixture containing organosilicon-modified isocyanate compounds, and 10-30 parts of a flame retardant; the polyurethane potting glue has excellent resistance to moisture and heat, and the physical property retention rate of the fully cured colloid after a double 85 test for 3000 hours can reach more than 90%, which can meet the technical requirements of the automotive battery pack for the colloid.

[0011] CN105504205A discloses a silicone polyurethane potting glue, which is composed of component A and component B by weight. Component A is diisocyanate, and component B is silicone-modified polyurethane. The cured product of the silicone polyurethane potting glue has outstanding weather resistance, can be used at -70°C to 130°C, has good adhesion to metals and plastics, and can be widely used in the sealing of electronic components such as industrial capacitors, control power supplies, ignition controllers, electronic sensor transformer coils, and circuit boards.

[0012] CN115322724A discloses an environment-friendly high-low temperature impact-resistant and weather-resistant two-component polyurethane potting sealant and a preparation method thereof. The sealant is composed of a component A and a component B in a mass ratio of 1:2-5. In parts by weight, the component A is composed of the following substances: a first isocyanate, a polyurethane prepolymer, a first plasticizer, and a water remover; the component B is composed of the following substances: an organosilicon-modified polyether polyol, a second plasticizer, a filler, and a catalyst. The environment-friendly high-low temperature impact-resistant and weather-resistant two-component polyurethane potting sealant of the invention is prepared by grafting an organosilicon segment onto a polyether polyol main chain to obtain an organosilicon-modified polyether polyol with a molecular weight of 1000-2000. The organosilicon-modified polyether polyol has good compatibility with materials such as polyurethane prepolymers and isocyanates in the polyurethane. After being placed, the polyurethane sealant will not be delaminated, and the construction performance of the polyurethane sealant is excellent.

[0013] CN114836167A discloses a low-viscosity, high-thermal-conductivity, flame-retardant two-component polyurethane potting glue and a preparation method thereof. The low-viscosity, high-thermal-conductivity, flame-retardant two-component polyurethane potting glue is composed of 30-40 parts of component A and 60-80 parts of component B in terms of mass fractions; component A is composed of 50-60 parts of polyurethane prepolymer, 20-30 parts of composite flame-retardant material and 10-15 parts of chlorinated paraffin in terms of mass fractions; component B is composed of vinyl-terminated silicone oil, thermal conductive filler, γ-glycidyl ether oxypropyl trimethoxy silane, aminotin catalyst, triethylenediamine, phthalic acid diester and silicone defoamer in terms of mass fractions. The low-viscosity, high-thermal-conductivity, flame-retardant two-component polyurethane potting glue of the present invention has low viscosity, is easy to operate, has an adjustable curing speed, and has excellent mechanical properties, flame retardant properties, thermal conductivity properties and electrical properties.

[0014] CN108219741A discloses a light organic silicon potting adhesive and a preparation method thereof. The light organic silicon potting adhesive of the invention is prepared from vinyl silicone oil and hydrogen-containing silicone oil as basic adhesives, hollow glass micropowder as volume filler, aluminum nitride as thermal conductive filler, and appropriate flame retardants, additives, etc. to form a light organic silicon thermal conductive flame retardant potting adhesive. The product has low density, high thermal conductivity, good flame retardancy, good comprehensive performance, and meets market development needs.

[0015] CN104277197A discloses a silicone-polyurethane potting adhesive and a preparation method thereof, and belongs to the technical field of sealants. The purpose of the present invention is to solve the problem that the traditional silicone-polyurethane potting adhesive has a low colloid silicon content and the modification effect of high temperature resistance and weather resistance is not obvious. The method of the present invention first prepares a silicone-polyurethane prepolymer containing -NCO, and then the prepolymer is chain extended and cured to form a silicone-polyurethane potting adhesive. The process of the present invention is simple and easy to operate, and the glue can be directly applied without dilution. It can still be used at a low temperature of -70°C, has good flexibility and an elongation at break of 550%-1200%. There is no decomposition at a high temperature of 130°C. The present invention can be used for the bonding of electronic devices with harsh working conditions, strong mechanical vibrations or large heat generation.

[0016] CN116003868A discloses a preparation process of power battery thermal insulation cotton with improved rebound rate, comprising the following steps: S1, selecting 45-65 parts by weight of polyurethane, 5-15 parts by weight of tetraethoxysilane, 2-10 parts by weight of foaming agent, 22-29 parts by weight of polyester polyol and 5-8 parts by weight of stabilizer and setting them aside; S2, using tetraethoxysilane as a precursor for gelation, aging, drying and modification to produce silica aerogel and setting them aside; S3, adding polyurethane, foaming agent, polyester polyol and stabilizer into a reactor in sequence and premixing them quickly to produce a premix; S4, applying the premix to both sides of the silica aerogel, and placing the silica aerogel in a molding box for preliminary curing to produce a blank; S5, taking out the blank, hot-pressing and molding the blank, and then trimming it to produce thermal insulation cotton with a specified shape. The foaming agents are sodium bicarbonate, salicylic acid and phthalic acid, and the weight ratio of sodium bicarbonate, salicylic acid and phthalic acid is 10:5:3. The stabilizers are sodium fatty alcohol ether sulfate and polyether modified silicone oil, and the weight ratio of sodium fatty alcohol ether sulfate and polyether modified silicone oil is 2:1. The drying process adopts supercritical drying technology. During supercritical drying, the pre-pressurization range is 7.0-9.0MPa, the supercritical temperature range is 250-275℃, and the supercritical pressure range is 10-12MPa. The thickness of the produced silica aerogel ranges from 2-8mm. However, the thermal insulation cotton of CN116003868A still cannot solve the problems of low bonding strength and inability to fully block the heat generated by leakage and fire of the battery cell, and thus cannot significantly improve the safety performance of the battery module.

[0017] In order to meet the application of polyurethane thermal conductive potting adhesive in the latest automotive battery packs, it is particularly urgent to improve the moisture and heat resistance and impact resistance of polyurethane thermal conductive potting adhesive.

[0018] In addition, for the potting glue used in existing new energy power batteries, when polyether polyols are used to prepare hard foam, the cured foam potting glue can meet the requirements of strength properties, but has a certain brittleness and poor stability at low temperatures (-20°C). When soft foam is used, it can meet the requirements of resilience, but the open porosity of the foam is too high (making the water absorption rate too high and the softness too high), poor stability at high temperatures (70°C), and the supporting force for fixing the battery pack in place is reduced, and the ability to resist impact and vibration will be reduced. Summary of the invention

[0019] In order to solve the technical problems existing in the prior art, the inventor of the present application first provides a fast-curing organic silicon-polyurethane composite potting material and a preparation method thereof, which is used for the assembly and packaging of new energy battery modules. The organic silicon-polyurethane material comprises two components, component A and component B. Components A and B are respectively contained in different sealed containers.

[0020] The silicone-polyurethane of the present invention has the properties of both polyurethane and silicone, and has the properties of being lightweight, waterproof, oxygen-isolating, shock-absorbing, sealing, mildew-proof, insulating, anti-aging, and flame-retardant. It can effectively block the heat generated by leakage and fire of the battery cell and improve the safety performance of the battery module.

[0021] The technical solution of the present invention combines the advantages of silicone materials and polyurethane materials to produce a potting adhesive that has the characteristics of high conductivity, resilience, tear resistance, high temperature resistance, insulation, etc. of silicone; at the same time, it also has the characteristics of light weight, shock resistance, low modulus, anti-vulcanization, and high bonding strength of polyurethane materials.

[0022] The inventor of the present application provides a silicone-polyurethane foam potting material (or foam potting material) (for batteries, new energy batteries, battery modules or new energy battery modules). The potting glue obtained by foaming and curing the potting material has a specific closed cell rate (that is, the appropriate open cell rate provides a small amount of resilience for the low-density potting glue), thereby meeting the requirements of potting glue used in the field of new energy vehicle batteries for strength and impact resistance and shock absorption.

[0023] In this application, "optional" means with or without.

[0024] According to a first embodiment of the present invention, a silicone-polyurethane foam potting material (for new energy batteries) (referred to as a potting composition) is provided, wherein the potting material comprises component A and component B or consists of components A and B:

[0025] Component A includes, by weight:

[0026] Polymer polyol: 45-55 parts, preferably 47-53 parts, preferably 48-52 parts, such as 50 parts;

[0027] Aqueous alcohol amine blowing agent: 3-10 parts; preferably 4-9.8 parts; preferably 5-9.5 parts; preferably 6-9 parts; for example 7, 7.5, 8 and 8.5 parts;

[0028] Catalyst: 0.4-2.0 parts; preferably 0.5-1.9 parts; 0.6-1.8 parts; 0.7-1.7 parts; 0.8-1.6 parts; such as 1 or 1.2 or 1.4 parts;

[0029] Halogen-free flame retardant: 7-35 parts; preferably 9-33 parts; 12-30 parts; 15-28 parts; 17-26 parts;

[0030] Foam stabilizer: 0.1-2 parts; preferably 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.5 parts; 0.6-1.3 parts; 0.7-1 parts;

[0031] Silane coupling agent: 0-2 parts; preferably 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.5 parts; 0.6-1.3 parts; 0.7-1 parts;

[0032] Chain extender: 0-4.5 parts; preferably 0.1-4.2 parts; 0.5-4.0 parts; 1-3.7 parts; 1.5-3.5 parts; 1.7-3.3 parts; 2-3 parts;

[0033] Antioxidant: 0-2.0 parts; preferably 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.6 parts; 0.6-1.5 parts;

[0034] Color paste: 0-1.0 part; preferably 0.1-0.8 part; 0.15-0.6 part; 0.2-0.5 part;

[0035] The polymer polyol comprises a sucrose-started polyether polyol (such as a sucrose-started polyoxypropylene polyol) and a sorbitol-started polyether polyol (such as a sorbitol-started polyoxypropylene polyol) or consists of the two, and the weight ratio of the sucrose-started polyether polyol to the sorbitol-started polyether polyol is (1.1-2):1, preferably (1.2-1.8):1, preferably (1.3-1.7):1;

[0036] Component B includes, by weight:

[0037] NCO-terminated polysiloxane-polyurethane prepolymer: 50-60 parts; preferably 52-58 parts; 54-56 parts; such as 55 parts;

[0038] Silicone oil: 4-20 parts; preferably 7-18 parts; preferably 9-16 parts; preferably 10-15 parts;

[0039] Diluent: 0-10 parts; preferably 3-9 parts; preferably 4-8 parts; preferably 5-7 parts;

[0040] The sum of the weight of the silicone oil and the diluent is 7-25 parts, preferably 9-23 parts, preferably 10-21 parts, such as 12, 14, 15, 17, 20 parts.

[0041] In the encapsulation application, the A component and the B component are mixed, stirred, foamed and encapsulated according to a weight ratio of 100:130-70 (i.e., 100:130 to 100:70), preferably, according to a weight ratio of 100:(125-75), preferably 100:(120-80), preferably 100:(115-85), preferably 100:(110-90), preferably 100:(105-95), preferably 100:100. That is, the A and B components are mixed, stirred, mixed according to the above ratio, and the mixture is poured into the battery module to be encapsulated, and it is foamed and encapsulated. After that, the encapsulated battery module is formed.

[0042] Preferably, the aqueous alcohol amine blowing agent comprises a mixture of isopropyl di-sec-butanolamine, isopropyl di-sec-butanolamine and water, and a portion of the alcohol amine is neutralized by CO2 so that the CO2 content in the aqueous alcohol amine blowing agent is 1-5wt%, preferably 1.2-4.8wt%, 1.5-4.5wt%, preferably 1.8-4.3wt%, preferably 2-4.5wt%, for example 3, 3.5, 4wt%, based on the total weight of the blowing agent. The molar ratio of isopropanol di-sec-butanolamine to isopropanol sec-butanolamine is (0.2-4): 1, preferably (0.25-3.8): 1, preferably (0.3-3.5): 1, preferably (0.4-3.2): 1, preferably (0.5-3.0): 1, preferably (0.6-2.8): 1, preferably (0.7-2.5): 1, preferably (0.8-2.2): 1, preferably (1.0-2.0): 1, preferably (1.2-1.8): 1, preferably 1.5: 1. In the blowing agent, the water content is 8-30wt%, preferably 10-28wt%, preferably 12-27wt%, preferably 14-26wt%, preferably 16-25wt%, preferably 18-24wt%, based on the total weight of the aqueous alcohol amine blowing agent.

[0043] Preferably, the total content of isopropanol di-sec-butanolamine, isopropanol sec-butanolamine and water in the blowing agent is 95-100%, preferably 95.5-100%, preferably 96-100%, such as 97, 98, 99, 99.5 or 99.8% or 99.9%, based on the total weight of the blowing agent; preferably, the balance is CO2.

[0044] The NCO-terminated polysiloxane-polyurethane prepolymer is formed by reacting (in molar excess) an organic polyisocyanate monomer (such as MDI, TDI, HDI and / or IPDI, or trimers thereof, or PMDI) with a polydimethylsiloxane diol (i.e., α,ω-dihydroxy polydimethylsiloxane, or hydroxy-terminated polydimethylsiloxane). Preferably, the hydroxyl equivalent weight (HEW) of the polydimethylsiloxane diol is in the range of 370-650 g / mol, preferably in the range of 400-600 g / mol, preferably 420-580 g / mol, preferably 440-560 g / mol, preferably 450-550 g / mol, preferably 460-540 g / mol, preferably 470-530 g / mol.

[0045] As for the silane coupling agent, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792,), and / or 3-aminopropyltriethoxysilane (KH-550) can be used. The use of the silane coupling agent can improve the bonding strength of the foam to the metal surface.

[0046] Compared with polyester polyols, sucrose-started polyether polyols (such as sucrose-started polyoxypropylene polyols) and sorbitol-started polyether polyols (such as sorbitol-started polyoxypropylene polyols) have the advantages of high bonding strength and hydrolysis resistance.

[0047] Preferably, the hydroxyl value of the sucrose-started polyether polyol (preferably sucrose-started polyoxypropylene polyol) is in the range of 290-450 mgKOH / g, preferably 300-440 mgKOH / g, more preferably 310-430 mgKOH / g, such as 320, 330, 350, 370, 400, 410, 420 mgKOH / g.

[0048] Preferably, the hydroxyl value of the sorbitol-started polyether polyol (preferably sorbitol-started polyoxypropylene polyol) is in the range of 340-520 mgKOH / g, preferably 350-490 mgKOH / g, such as 360, 370, 380, 400, 450, 470, 500 mgKOH / g.

[0049] Commonly used catalysts are selected from: 33LV (A-33): 33% triethylenediamine in dipropylene glycol solution, N,N-dimethylethanolamine, N,N-dimethylbenzylamine, 70% bis(dimethylaminoethyl) ether in dipropylene glycol solution, 70% potassium octoate in diethylene glycol solution, dibutyltin dilaurate, PT303, PT304, potassium acetate, PC-8 (N,N-dimethylcyclohexylamine), PC-5 (N,N,N,N,N-pentamethyldiethylenetriamine), PC-41 (tris(dimethylaminopropyl)hexahydrotriazine), triethanolamine, JXP-508, JXP-509, TMR-2 (2-hydroxy-N,N,N-trimethyl-1-propylamine formate, Air Products and Chemicals, USA), TMR-3, TMR-4, Dabco 2040 (Evonik Chemicals).

[0050] Preferably, the catalyst is one or more of N,N-dimethylcyclohexylamine, N,N-dimethylbenzylamine, bis(dimethylaminoethyl) ether, and dibutyltin dilaurate.

[0051] Preferably, the halogen-free flame retardant is one or more of dimethyl methylphosphonate, diethyl ethyl phosphate, triethyl phosphate, isopropylated triphenylphosphonate, triphenyl phosphate, melamine, magnesium hydroxide, ammonium polyphosphate, red phosphorus, expanded graphite, and antimony dioxide. It does not contain halogen and can reduce corrosion to metal parts.

[0052] Preferably, the foam stabilizer is one or more of polymethylsiloxane, amino-modified siloxane, epoxy-modified siloxane, polyether-modified siloxane and sulfur-modified siloxane.

[0053] The chain extender is one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, hydroquinone dihydroxyethyl ether and resorcinol dihydroxyethyl ether.

[0054] The antioxidant is one or more of poly(dipropylene glycol) phenyl phosphite, tris(2,4-di-tert-butylphenyl) 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate phosphite, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0055] The color paste is one of oily polyether type black paste, yellow paste, red paste, blue paste, green paste and gray paste.

[0056] The organic polyisocyanate is MDI (diphenylmethane diisocyanate), PMDI (polymethylene polyphenyl polyisocyanate, such as PM200 of Wanhua Chemical), TDI (toluene diisocyanate), HDI (hexamethylene diisocyanate) and / or IPDI (isophorone diisocyanate).

[0057] Preferably, the silicone oil is dimethyl silicone oil. Silicone oil has the function of plasticizing and reducing viscosity, and is also beneficial to improving the hydrophobicity of the potting material.

[0058] Preferably, the diluent is one or more of dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, and tributyl citrate.

[0059] According to a second embodiment of the present invention, a method for preparing (or preparing) the above-mentioned silicone-polyurethane foam potting material (hereinafter referred to as potting composition) is provided, the method comprising:

[0060] Add polymer polyol (i.e., sucrose-initiated polyether polyol and sorbitol-initiated polyether polyol), halogen-free flame retardant, foam stabilizer, optional silane coupling agent, optional chain extender, optional antioxidant, and optional color paste into a reaction kettle, heat the reaction kettle to 105-120° C. (e.g., 110° C.) under stirring to dissolve all the materials in the kettle, evacuate the kettle to negative pressure (e.g., start a vacuum device to evacuate the kettle. Evacuate the kettle to a pressure of, for example, -0.7 MPa to -0.95 MPa, such as -0.8 to -0.9 MPa), and keep the temperature and pressure (i.e., keep the temperature and vacuum degree for 40-200 min, such as 60-150 min, such as 80 min); then, cool the reaction kettle to room temperature, release the pressure, add a blowing agent and a catalyst, and mix (e.g., 30-180 min, such as 40-150 min, 60-80 min) to obtain component A.

[0061] Add the NCO-terminated polysiloxane-polyurethane prepolymer, silicone oil and optional diluent into a reaction kettle, stir, heat the contents in the kettle to 95-105° C. (e.g., 100° C.) and keep the temperature constant for 30-200 min (e.g., 45-150 min, e.g., 60-80 min), evacuate the kettle to negative pressure (e.g., start a vacuum device to evacuate the kettle. Evacuate the kettle to a pressure of, for example, -0.7 MPa to -0.95 MPa, e.g., -0.8 to -0.95 MPa). 9MPa), keep the temperature and pressure at the temperature and pressure (i.e., keep the temperature at 95-105°C, such as 100°C and the pressure in the kettle at, for example, -0.7MPa to -0.95MPa, such as -0.8 to -0.9MPa) for a period of time, such as 40-180min, such as 50-150min, such as 60-80min), release the pressure, cool the contents in the kettle (for example, cool the contents in the kettle to 15-40°C, preferably 25-35°C, such as 30°C), and obtain component B.

[0062] The above-mentioned component A and component B are respectively placed in respective containers to obtain a two-component silicone-polyurethane (foam) potting material (referred to as potting composition).

[0063] A method for potting a battery module using the above-mentioned silicone-polyurethane foam potting material (hereinafter referred to as potting composition), the potting method comprising:

[0064] According to the weight ratio of component A and component B of 100:130-70 (i.e. 100:130 to 100:70), preferably, according to the weight ratio of 100:(125-75), preferably 100:(120-80), preferably 100:(115-85), preferably 100:(110-90), preferably 100:(105-95), preferably 100:100 (the weighed mass is calculated according to the bulk density of 280), components A and B are mixed and stirred, and the resulting mixture is poured into the battery module to be encapsulated, and it is foamed and encapsulated.

[0065] The present invention also provides a battery module, wherein the above-mentioned encapsulation material is used for encapsulation and molding.

[0066] Advantages of the present invention

[0067] 1. The present invention selects sucrose-based polyether polyol and sorbitol-based polyether polyol with excellent hydrolysis resistance as the main components of component A, so that the foam potting glue has excellent hydrolysis resistance and bonding strength. These two polyether polyols have been mass-produced in many enterprises in my country, and the raw materials are easy to obtain. Therefore, the use of these two raw materials can reduce the production cost of the potting material.

[0068] 2. The inventors selected a mixture of isopropyl alcohol di-sec-butanolamine, isopropyl alcohol sec-butanolamine and water partially neutralized by CO2 as a foaming agent (i.e., an aqueous alcohol amine foaming agent) from a series of new foaming agents developed by Butian New Materials Technology Co., Ltd. The isopropyl alcohol sec-butanolamine present in the foaming agent is used to absorb CO2. Among them, isopropyl alcohol di-sec-butanolamine is used as a cross-linking agent and isopropyl alcohol sec-butanolamine is used as a chain extender, thereby improving the strength of the potting glue. The introduction of butyl in the foam can add a certain degree of flexibility to the foam and reduce the brittleness of the foam prepared from polyether polyols.

[0069] 3. Isopropyl alcohol di-sec-butanolamine and isopropyl alcohol sec-butanolamine have asymmetric structures. They are mixed with each other, so that the aqueous alcohol amine foaming agent has a lower viscosity. In addition, the foaming agent and the polyether polyol have excellent compatibility and miscibility with each other, making the resulting foam more delicate (the size of the pores is smaller and more uniform).

[0070] 4. When the water content in the aqueous alcohol amine foaming agent is greater than 8wt%, preferably greater than 15wt%, and more preferably greater than 18wt%, a portion of the water reacts with the isocyanate group during the foaming process, thereby generating a suitable open cell rate in the cured potting foam. Accordingly, the closed cell rate of the potting foam is controlled within a suitable range (e.g., within the range of 93-95%), which enables the potting foam to have an adaptive rebound rate, thereby reducing the brittleness of the foam, increasing toughness or elasticity, having excellent high temperature stability and low temperature stability, and being able to fully resist the effects of impact and vibration.

[0071] When the water content in the aqueous alcohol amine blowing agent is less than 8 wt%, the brittleness of the resulting foam will increase and its low temperature stability will deteriorate.

[0072] In addition, the content of CO2 in the aqueous alcohol amine foaming agent should not be too high, for example, should not be higher than 6wt%. If the content of CO2 is too high, the heat of reaction in the foaming reaction causes a large amount of CO2 to be violently released and expanded, and water has almost no chance to participate in the foaming reaction in the early stage of the foaming reaction, thereby affecting the structure of the foam, and further affecting the toughness and strength of the foam.

[0073] 5. The activity of polydimethylsiloxane diol (i.e., α, ω-dihydroxy polydimethylsiloxane) in reacting with isocyanate is slightly low, which affects the curing speed of the potting material. However, if it is made into an NCO-terminated polyurethane prepolymer in advance, the curing rate can be increased. The use of amino-containing silane coupling agents can improve the bonding strength of the potting compound to the metal. Dimethyl silicone oil is used to reduce the viscosity of component B. The use of these three silicon-containing raw materials is conducive to improving the hydrophobicity and weather resistance of the potting compound.

[0074] 6. The silicone-polyurethane potting material of the present invention has the characteristics of both polyurethane and silicone, and can effectively block the heat generated by leakage and fire of battery cells, greatly improving the safety performance of battery modules. During the driving process of new energy vehicles, the battery modules are frequently subjected to impact and vibration, as well as cold and heat shocks in winter and summer, battery cell leakage, etc. Therefore, there are quite high requirements for the bonding strength, heat resistance, impact resistance, weather resistance, etc. of the potting glue under harsh conditions. The potting material (potting glue foam) of the present invention has excellent bonding strength to various components in the battery module, and the potting glue foam has sufficient flexibility, resilience, flame retardancy, thermal insulation, and weather resistance to meet these strict requirements.

[0075] 7. The potting material has a low thermal conductivity. The potted battery module can block heat conduction during thermal runaway and control heat spread. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 This is a SEM photograph of the potting foam of Example 1.

[0077] Figure 2 This is a SEM photo of the potting foam of Example 2.

[0078] Figure 3 This is a SEM photograph of the potting foam of Comparative Example 1.

[0079] Figure 4 The sample of the olamine product of Synthesis Example 3 is 1 H-NMR spectrum. DETAILED DESCRIPTION

[0080] The present invention further describes the technical scheme in detail through the following examples, but the present invention is not limited to these examples.

[0081] Unless otherwise specified, the devices and materials used in the examples are those commonly used in the art and commercially available on the market.

[0082] Method for measuring the content of alcoholamines: In the embodiments, the method for measuring the content of various alcoholamines (e.g., isopropanol di-sec-butanolamine, isopropanol sec-butanolamine) in the aqueous alcoholamine mixture (AC) (or aqueous alcoholamine composition or alcoholamine hydrate) can be performed by gas chromatography, wherein the gas chromatograph is equipped with a hydrogen flame ionization detector (FID), and the mass concentration of the alcoholamine compound is about 10 mg / mL, which is a standard solution. Gas chromatography conditions: HP-5 capillary column (30m×0.32mmi.d.×0.25μm, 5% phenyl methyl-siloxane); the column temperature was programmed, the initial temperature was 80℃, maintained for 3min, then increased to 250℃ at a rate of 25℃ / min, and maintained for 5min; the injection port temperature was 250℃; the detector temperature was 260℃; the carrier gas was high-purity nitrogen with a flow rate of 1.5mL / min; the fuel gas was hydrogen with a flow rate of 30mL / min; the auxiliary gas was air with a flow rate of 300mL / min; the tail gas was nitrogen with a flow rate of 25mL / min; the injection method was split injection, with a split ratio of 30:1; the injection volume was 1μL.

[0083] In the present application, as a sucrose-started polyether polyol having a hydroxyl value between 290 and 450 mg KOH / g, polyether polyol 8310 (sucrose initiator, hydroxyl value 310 mg KOH / g) of BEFAR GROUP CO., LTD., polyether polyol H4110S (hydroxyl value 400-420 mg KOH / g) and H4520 (hydroxyl value 335-365 mg KOH / g) of Hongbaoli Group Co., Ltd., and polyether polyol YD-8238 (hydroxyl value 385 ± 10 mg KOH / g) and YD-889 (hydroxyl value 405 ± 10 mg KOH / g) of Hebei Yadong Chemical Group Co., Ltd. can be used.

[0084] As the sorbitol-started polyether polyol with a hydroxyl value between 340 and 520 mgKOH / g, polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g) of Jiahua Chemical Co., Ltd., polyether polyol H5021 (hydroxyl value 355-385 mgKOH / g) and H635SG (hydroxyl value 485-515 mgKOH / g) of Hongbaoli Group Co., Ltd., and polyether polyol YD-635 (hydroxyl value 490±15 mgKOH / g) and YD-6205 (hydroxyl value 380±15 mgKOH / g) of Hebei Yadong Chemical Group Co., Ltd. can be used.

[0085] As polysiloxane diols having a hydroxyl equivalent weight (HEW) between 400 and 600 g / mol (e.g., polydimethylsiloxane diol, α,ω-dihydroxy polydimethylsiloxane, or terminal hydroxyl polydimethylsiloxane), hydroxyl-terminated polysiloxanes MCR-C61 (hydroxyl equivalent HEW = 500 g / mol, functionality 2) and MCR-62 (hydroxyl equivalent 2500 g / mol, functionality 2) from Gelest, USA, and Silmer OH Di-100 (hydroxyl equivalent 3500 g / mol, functionality 2) from Sil TECH can be used. In addition, other polysiloxanes for rigid polyurethane foams can also be used, such as B 8465, B8462, B ​​8467, B 8461, B 8516, B 8476 produced by Degussa, L-6900, L-6910, L-6915, L-6920, L-6980, L-5440 produced by Crompton, SS8005, SS8002 produced by Saxol, DC5950, DC193, DC1598 produced by Air Products, etc. Products produced by Zhejiang Xin'an Chemical Group Co., Ltd., for example, linear polydimethylsiloxane with terminal hydroxyl groups having a molecular weight of 300 to 500.

[0086] As the foam stabilizer, one or more of polymethylsiloxane, amino-modified siloxane, epoxy-modified siloxane, polyether-modified siloxane, and sulfur-modified siloxane can be used. In addition, the following silicone oil-type foam stabilizers or silane surfactants can also be used: B8525 and B8408 of Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 of Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 of Gas and Chemicals, and silicone oil 8841 of Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 of Gas and Chemicals.

[0087] The test methods for various parameters of silicone-polyurethane potting foam are carried out with reference to the following Chinese national standards GB:

[0088]

[0089] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the substrate), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.

[0090] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 25°C.

[0091] The 5% thermal weight loss temperature of the encapsulant was measured using a Mettler differential thermal-thermogravimetric analyzer.

[0092] Synthesis example 1

[0093] 10 kg of hydroxyl-terminated polysiloxane MCR-C61 (hydroxyl equivalent HEW=500 g / mol, functionality 2, Gelest Company, USA) and 2.5 kg of isocyanate MDI (Wanhua Chemical) were mixed at 60° C. under nitrogen atmosphere protection and stirred at a stirring speed of 450 rpm for 0.5 hour, then the temperature was raised to 70° C. to continue the reaction until the NCO content of the reaction product was 3.8%, thereby obtaining an NCO-terminated polysiloxane-polyurethane prepolymer (prepolymer 1).

[0094] Synthesis example 2

[0095] Part I: Preparation of single alcohol amines

[0096] 1) 37.56 kg of isopropanolamine (molecular weight 75.11, 500 mol) and 16.6 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.25 MPa. 36.06 kg of 1,2-butylene oxide (500 mol, the molar ratio of 1,2-butylene oxide to isopropanolamine was 1:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40°C. Then, 90.02 kg of the reaction product (alcoholamine hydrate AA1a) was discharged from the reactor. Samples were taken from the product and the content of isopropanol sec-butanolamine in the alcoholamine hydrate AA1a was measured by gas chromatography to be 499.85 mol and 0.15 mol. Its viscosity (25°C) was 407 centipoise. The water content of the alcoholamine hydrate AA1a was 18.4 wt %. The pH value was 11.87.

[0097] 2) 37.56 kg of isopropanolamine (molecular weight 75.11, 500 mol) and 23.5 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.25 MPa. 72.11 kg of 1,2-butylene oxide (1000 mol, the molar ratio of 1,2-butylene oxide to isopropanolamine was 2:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40°C. Then, 133 kg of the reaction product (alcoholamine hydrate AA1b) was discharged from the reactor. Samples were taken from the product and the content of isopropanol di-sec-butanolamine in the alcoholamine hydrate AA1b was measured by gas chromatography to be 499.87 mol and 0.13 mol. Its viscosity (25°C) was 519 centipoise. The water content of the alcoholamine hydrate AA1b was 17.6 wt %. The pH value was 11.12.

[0098] Part 2: Compounding of Alkylamines

[0099] Four batches of 20 kg each were taken from 90 kg of the reaction product (alkanolamine hydrate AA1a). For each batch, 20 kg of alkanolamine hydrate AA1a (isopropanol sec-butanolamine) was added to an autoclave, and then alkanolamine hydrate AA1b (isopropanol di-sec-butanolamine) and water were added and mixed according to the molar ratio and water content in Table 1 below to obtain four batches of alkanolamine compositions AC (AA2a-AA2d).

[0100] Table 1: Molar ratio of isopropanol di-sec-butanolamine to isopropanol sec-butanolamine

[0101] Alcoholamine hydrate No The molar ratio of isopropanol di-sec-butanolamine to isopropanol sec-butanolamine Water content wt% Alcoholamine composition AA2a 3:1 19.0 Alcoholamine composition AA2b 1:1 19.0 Alcoholamine composition AA2c 0.5:1 19.0 Alcoholamine composition AA2d 1:1 19.0

[0102] Part 3: CO2 Neutralization and Salt Formation

[0103] The four batches of alcohol amine hydrates AA2a-AA2d obtained by the above compounding were added to the autoclave respectively, and the carbonic acid alcohol amine salt compositions AA3a-AA3d (or carbonate alcohol amine salt compositions 1-4) were obtained by controlling the CO2 output from the CO2 storage cylinder under the condition that the pressure of the gas was not higher than 0.3MPa. The temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours. The pressure was released after the temperature was lowered to below 40°C, and then a small amount of water was added to make the water content in the carbonate alcohol amine salt composition reach 21wt%, and the mixture was slowly stirred for 30 minutes, and the product was discharged. The CO2 content was shown in Table 2.

[0104] Table 2: CO2 content in carbonate amine salt compositions

[0105]

[0106] Synthesis example 3

[0107] 24.64 kg of ethanolamine (molecular weight 61, 404 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled to be no higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.64 kg of the reaction product (alcoholamine hydrate AA4a, or alcoholamine composition AA4a) was discharged from the reactor, and the viscosity (25° C.) was 288 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA4a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.9 mol, the content of ethanol diisopropanolamine was 323.1 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 4 The water content of the alcoholamine hydrate AA4a was determined by Karl Fischer method to be 15.6 wt %.

[0108] Then, 40 kg of the above obtained alcohol amine hydrate AA4a is added to the autoclave, and carbon dioxide gas is introduced into the alcohol amine hydrate AA4a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is controlled to be not higher than 0.3 MPa, and the temperature is controlled between 40-50°C, and the temperature is controlled to react for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcohol amine salt composition AA4b (or referred to as alcohol amine composition AA4b), wherein the CO2 absorption is 1.76 kg (about 40 mol; CO2 content is 4.2 wt%). The dynamic viscosity (25°C) of the product AA4b is 792 centipoise. The pH of the product AA4b measured by a pH meter (Ray Magnetic PHS-3C type, Shanghai Yidian Science Instrument Co., Ltd.) is 10.6. Its decomposition temperature is between 45°C and 60°C.

[0109] Example 1

[0110] 3.0 kg of polyether polyol 8310 (sucrose initiator, hydroxyl value 310 mg KOH / g, Binhua Group Co., Ltd.), 2.0 kg of polyether polyol 8038 (sorbitol initiator, hydroxyl value 380 mg KOH / g, Jiahua Chemical Co., Ltd.), 0.25 kg of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.), 1 kg of dimethyl methylphosphonate and 1 kg of melamine (halogen-free flame retardant), 0.15 kg of foam stabilizer DC3201 (Gas and Chemicals Company), 0.01 kg of 1,4-butanediol as a chain extender, and 0.1 kg of antioxidant poly(dipropylene glycol) phenyl phosphite were added into the reactor, stirring was started, and the speed was increased to 200 rpm. Set to 100 rpm, turn on the heating device to heat the material in the kettle to 110°C, then maintain the constant temperature for 60 minutes, turn on the vacuum device until the pressure in the kettle is -0.9MPa, keep the temperature and pressure for 80 minutes, release the pressure (release the vacuum), cool the material in the kettle to 30-35°C, add 0.1kg of catalyst N,N-dimethylcyclohexylamine and 0.9kg of carbonate amine salt composition 1 (AA3a) as an aqueous alcoholamine foaming agent, and mix for another 60 minutes to obtain component A with a viscosity (25°C) of 1574mPa.s.

[0111] 5.0 kg of NCO-terminated polysiloxane-polyurethane prepolymer (prepolymer 1), 1.3 kg of dimethyl silicone oil (GB201-350, Jinan Silicon Port Chemical Co., Ltd.) and 0.2 kg of dimethyl phthalate were added to the reaction kettle, stirring was started, the speed was set to 100 rpm, the heating device was turned on, the temperature of the materials in the kettle was raised to 100°C, and the constant temperature was maintained for 60 minutes. The vacuum device was turned on until the pressure in the kettle was -0.9 MPa. After keeping the temperature and pressure for 60 minutes, the pressure was released and the temperature of the materials in the kettle was lowered to 30°C to obtain component B.

[0112] The component A and component B prepared by the above method are mixed in a weight ratio of 100:100, wherein the weight is calculated according to the bulk density of 280; the stirrer is turned on and the stirrer speed is set at 2800 rpm, mixed for 20 seconds, and the mixture is poured into the lithium-ion battery module to be potted, foamed, and potted. The potted battery module is thus formed.

[0113] At the same time, in order to test the performance of the potting compound, the mixture was poured into a plastic box and allowed to foam and solidify. Then the performance of the potting compound was analyzed by sampling, and the measured properties are listed in Table 3. The thermal conductivity (w / m·k, 22.5°C) is 0.02215. The flame retardancy meets the UL94-V0 standard. The temperature of 5% thermal weight loss is 245°C. The SEM photo of the foam sample is shown in Figure 1 In the experiment, the size of the pores is uniform, the outline of the pores is clear, and the integrity is good.

[0114] The 5% thermal weight loss temperature of the potting compound is 245°C, indicating that it has good heat resistance.

[0115] Example 2

[0116] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 2 (AA3b) was used instead of carbonate alcohol amine salt composition 1 (AA3a). The SEM photograph of the foam sample is shown in Figure 2 middle,

[0117] Example 3

[0118] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 3 (AA3c) was used instead of carbonate alcohol amine salt composition 1 (AA3a).

[0119] Comparative Example 1 (Com.Ex 1)

[0120] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 4 (AA3d) (water content 34 wt%) was used instead of carbonate alcohol amine salt composition 1 (AA3a). The SEM photograph of the foam sample is shown in Figure 3 In the embodiment, the size of the pores is uneven, and the number of through pores is large (higher open porosity).

[0121] Comparative Example 2 (Com.Ex.2)

[0122] 1.0 kg of carbonate alcohol amine salt composition AA4b (water content of about 15 wt%) was measured and water was added thereto under stirring to dilute it to 19.0 wt% water content to obtain carbonate alcohol amine salt composition AA4b with 19.0 wt% water content. Example 1 was repeated except that the same amount (0.9 kg) of carbonate alcohol amine salt composition AA4b with 19.0 wt% water content was used instead of carbonate alcohol amine salt composition 1 (AA3a).

[0123] Table 3-Performance parameters of potting foam

[0124]

[0125] Note: The compressive strength is measured on the foam specimen in the Z direction (perpendicular to the substrate).

[0126] It can be seen from the data in Table 3 above that the closed cell rate of the potting glue of Comparative Example 1 is too low, the water absorption rate is too high, especially the rebound rate is too high (soft), the high temperature stability (dimensional stability%, 70°C) is poor (up to 1.55), and the low temperature stability (dimensional stability%, -20°C) is not very good (0.47). It cannot effectively reduce the impact and vibration of the battery pack during the operation of the new energy vehicle, resulting in the battery unit cannot be fixed in place.

[0127] The potting compound of Comparative Example 2 has high hardness, slightly greater brittleness (lower rebound rate), and slightly poor low-temperature stability (dimensional stability%, -20°C) (up to 0.42).

[0128] The potting compound of Example 1 is compared with the potting compound of Comparative Example 2, which shows that the combination of isopropyl alcohol di-sec-butanolamine and isopropyl alcohol di-sec-butanolamine in Example 1, compared with the combination of ethanol diisopropanolamine and ethanol isopropanolamine in Comparative Example 2, introduces a butyl group with a longer chain length into the foam, which can improve the brittleness of the foam and increase the toughness of the foam. The high temperature stability and low temperature stability of the potting compound of Example 1 are better than those of the potting compound of Comparative Example 2.

[0129] The potting glue of Examples 1-3 of the present invention has a suitable closed-cell rate and rebound rate (8-11%), takes into account both strength and toughness, has good stability at high and low temperatures, and fully exerts its protective effect on the battery. In addition, the potting glue of Examples 1-3 has a low water absorption rate, that is, it has a high hydrophobicity, and can fully prevent the penetration and diffusion of leakage liquid (such as battery cell leakage) of the battery module.

[0130] When using sucrose-started polyether polyols and sorbitol-started polyols, which are easily available raw materials, by using the aqueous alcohol amine foaming agent and silicon-containing raw materials, the potting glue of Examples 1-3 of the present invention can effectively enhance the integrity of the battery module, has good ability to resist impact and vibration, and improves the insulation performance between electronic components and circuits.

Claims

1. An organosilicon-polyurethane foam potting material, the potting material consisting of component A and component B, wherein: Component A includes (by weight): polymer polyol: 45-55 parts; Aqueous alcohol amine foaming agent: 3-10 parts; Catalyst: 0.4-2.0 parts; Halogen-free flame retardant: 7-35 parts; Foam stabilizer: 0.1-2 parts; Silane coupling agent: 0-2 parts; Chain extender: 0-4.5 parts; Antioxidant: 0-2.0 parts; Color paste: 0-1.0 parts; The polymer polyol is composed of sucrose-started polyether polyol and sorbitol-started polyether polyol, and the weight ratio of sucrose-started polyether polyol to sorbitol-started polyether polyol is (1.1-2):1; The aqueous alcohol amine foaming agent comprises a mixture of isopropyl alcohol di-sec-butanolamine, isopropyl alcohol sec-butanolamine and water, the content of water is 8-30wt%, and the total content of isopropyl alcohol di-sec-butanolamine, isopropyl alcohol sec-butanolamine and water is 95-100%, a part of the alcohol amine is neutralized by CO2 so that the content of CO2 in the aqueous alcohol amine foaming agent is 1-5wt%, based on the total weight of the foaming agent; the molar ratio of isopropyl alcohol di-sec-butanolamine to isopropyl alcohol sec-butanolamine in the foaming agent is (0.2-4):1; Component B includes (by weight): NCO-terminated polysiloxane-polyurethane prepolymer: 50-60 parts; silicone oil: 4-20 parts; diluent: 0-10 parts; wherein the sum of the weight of silicone oil and diluent is 7-25 parts; When used for potting, component A and component B are mixed in a weight ratio of 100:130-70, stirred, foamed and potted.

2. The potting material according to claim 1, wherein: Component A includes, by weight: polymer polyol: 47-53 parts, preferably 48-52 parts, such as 50 parts; aqueous alcohol amine blowing agent: 4-9.8 parts; preferably 5-9.5 parts; preferably 6-9 parts; for example 7, 7.5, 8 and 8.5 parts; catalyst: 0.5-1.9 parts; 0.6-1.8 parts; 0.7-1.7 parts; 0.8-1.6 parts; such as 1 or 1.2 or 1.4 parts; halogen-free flame retardant: 9-33 parts; 12-30 parts; 15-28 parts; 17-26 parts; Foam stabilizer: 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.5 parts; 0.6-1.3 parts; 0.7-1 parts; Silane coupling agent: 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.5 parts; 0.6-1.3 parts; 0.7-1 parts; Chain extender: 0.1-4.2 parts; 0.5-4.0 parts; 1-3.7 parts; 1.5-3.5 parts; 1.7-3.3 parts; 2-3 parts; Antioxidant: 0.3-1.8 parts; 0.4-1.7 parts; 0.5-1.6 parts; 0.6-1.5 parts; Color paste: 0.1-0.8 parts; 0.15-0.6 parts; 0.2-0.5 parts; Component B includes, by weight: NCO-terminated polysiloxane-polyurethane prepolymer: 52-58 parts; 54-56 parts; such as 55 parts; Silicone oil: 7-18 parts; preferably 9-16 parts; preferably 10-15 parts; Diluent: 3-9 parts; preferably 4-8 parts; preferably 5-7 parts; wherein the sum of the weight of silicone oil and diluent is 9-23 parts, preferably 10-21 parts, for example 12, 14, 15, 17, 20 parts.

3. The potting material according to claim 1 or 2, wherein: When used for encapsulation, component A and component B are mixed, stirred, foamed and encapsulated in a weight ratio of 100:(125-75), preferably 100:(120-80), preferably 100:(115-85), preferably 100:(110-90), preferably 100:(105-95), preferably 100:

100.

4. The potting material according to any one of claims 1 to 3, wherein: The CO2 content of the aqueous alcohol amine blowing agent is 1.5-4.5wt%, preferably 1.8-4.3wt%, preferably 2-4.5wt%, based on the total weight of the blowing agent; and / or The molar ratio of isopropanol di-sec-butanolamine to isopropanol sec-butanolamine is (0.25-3.8):1, preferably (0.3-3.5):1, preferably (0.4-3.2):1, preferably (0.5-3.0):1, preferably (0.6-2.8):1, preferably (0.7-2.5):1, preferably (0.8-2.2):1, preferably (1.0-2.0):1, preferably (1.2-1.8):1, preferably 1.5:1; and / or In the blowing agent, the content of water is 10-28 wt %, preferably 12-27 wt %, preferably 14-26 wt %, preferably 16-25 wt %, preferably 18-24 wt %, based on the total weight of the aqueous alcoholamine blowing agent.

5. The potting material according to any one of claims 1 to 4, wherein: The NCO-terminated polysiloxane-polyurethane prepolymer is formed by the reaction of an organic polyisocyanate monomer and α,ω-dihydroxy polydimethylsiloxane; Preferably, the hydroxyl equivalent weight (HEW) of the polydimethylsiloxane diol is in the range of 370-650 g / mol, preferably in the range of 400-600 g / mol, preferably 420-580 g / mol, preferably 440-560 g / mol, preferably 450-550 g / mol, preferably 460-540 g / mol, preferably 470-530 g / mol.

6. The potting material according to any one of claims 1 to 5, wherein: The hydroxyl value of the sucrose-started polyether polyol is in the range of 290-450 mgKOH / g, preferably 300-440 mgKOH / g, more preferably 310-430 mgKOH / g; and / or The hydroxyl value of the sorbitol starting polyether polyol is in the range of 340-520 mgKOH / g, preferably 350-490 mgKOH / g.

7. The potting material according to any one of claims 1 to 6, wherein: The silicone oil is dimethyl silicone oil; and / or The organic polyisocyanate is diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, toluene diisocyanate, hexamethylene diisocyanate and / or isophorone diisocyanate; and / or The halogen-free flame retardant is one or more of dimethyl methylphosphonate, diethyl ethyl phosphate, triethyl phosphate, isopropylated triphenylphosphonate, triphenyl phosphate, melamine, magnesium hydroxide, ammonium polyphosphate, red phosphorus, expanded graphite, and antimony dioxide.

8. A method for preparing a silicone-polyurethane foam potting material, the method comprising: Add polymer polyol, halogen-free flame retardant, foam stabilizer, optional silane coupling agent, optional chain extender, optional antioxidant, and optional color paste into a reaction kettle, heat to 105-120° C. under stirring to dissolve all the materials in the kettle, evacuate the kettle to negative pressure, and keep the temperature and pressure; then, cool to room temperature, release the pressure, add a foaming agent and a catalyst, and mix again to obtain component A. Add NCO-terminated polysiloxane-polyurethane prepolymer, silicone oil and optional diluent into a reaction kettle, stir, heat the contents in the kettle to 95-105°C and keep the temperature constant for 30-200 minutes, evacuate the kettle to negative pressure, maintain the temperature and pressure at the temperature and pressure, release the pressure, cool the contents in the kettle, and obtain component B. The above-mentioned component A and component B are respectively placed in respective containers to obtain a two-component silicone-polyurethane foam potting material.

9. A battery module, wherein the battery module is potted and molded using the potting material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Organic silicon-polyurethane potting glue and preparation method thereof

    CN104277197A

  • Polysiloxane-polyurethane potting adhesive and preparation method thereof

    CN105504205A

  • Light organosilicon pouring sealant and preparation method thereof

    CN108219741A

  • Low-viscosity high-thermal-conductivity flame-retardant two-component polyurethane pouring sealant and preparation method thereof

    CN114836167A

  • Environment-friendly weather-resistant bi-component polyurethane potting sealant with high and low temperature impact resistance and preparation method thereof

    CN115322724A

Cited By

  • All-water foaming organic silicon polyurethane foam material and preparation method thereof

    CN120137129A

  • Optical sensor package structure and electronic device

    US12388064B2

  • Optical sensor package structure and electronic device

    US20230246012A1